Emergence of apple leafcurling midge (Dasineura mali) and its parasitoid (Platygaster demades) - Tomkins, A.R; Wilson, D.J.; Thomson, C.; Bradley, S.; Cole, L.; Shaw, P.; Gibb, A.; Suckling, D.M.; Marshall, R.; Wearing, C.H. (New Zealand Plant Protection, 2000)
Apple leafcurling midge (Dasineura mali) (ALCM) can seriously damage apple tree leaves Insecticides may be applied to the soil in spring to kill ALCM emerging from overwintering sites ALCM emergence was studied in the Waikato Hawkes Bay Nelson Canterbury and Central Otago over two seasons (1998/99 and 1999/ 2000) using cages placed over the soil beneath apple trees ALCM and its egg parasitoid (Platygaster demades) emerged over a similar period of time Emergence in southern districts began later and over a shorter period A single soil treatment with diazinon reduced the numbers of ALCM emerging from treated soil but also very few P demades emerged